Standarisasi Spesifik dan Non Spesifik Simplisia dan Ekstrak Etanol Bawang Putih Tunggal Terfermentasi (Allium sativum Linn.) - Vernanda, Renna Yulia; Puspitasari, Maria Revina; Satya, Hadianto Nur (Jurnal Farmasi Sains dan Terapan (Journal of Pharmacy Science and Practice), 2019)
Garlic that has undergo a fermentation process (Black garlic) has been shown to have a total content of flavonoids and polyphenols greater than fresh garlic. One of garlic varieties is single bulb Garlic (Allium sativum Linn.) which contains only one small bulb. This study aims to determine specific and non specific standardization of dried fermented single bulb Garlic and ethanol extract of fermented single bulb Garlic (Allium sativum Linn.). Samples were collected from three different regions: Temanggung, Bromo and Banyuwangi. The results of the study showed that dried fermented single bulb garlic have round shape oval, brown color blackish, and aromatic odor; water soluble content >25%, ethanol soluble content >26%, total polyphenols >4.5% b/b, total flavonoids >0.6% b/b; dred fermented single bulb Garlic contain polyphenols, flavonoids, and saponins; total ash content 2% b/b; the ethanol extract contain polyphenols and flavonoids; total ash content